Prospects of Green Marketing in Bangladesh: An Empirical Study on Green Marketing - Ehasan, Md. Amimul (Global Disclosure of Economics and Business, 2020)
The awareness of environmental degradation has been a long time coming to Bangladesh. In recent years, environmental issues in Bangladesh have received much attention, reflecting rising public concern and awareness of environmental problems. Pressure groups have been campaigning vigorously for the environment and media reporting on environmental issues has increased dramatically. It has also moved up on the agenda in political decision making and numerous laws and regulations were enacted for the protection of environment. Moreover, through the earth summit in Rio de Janeiro in 1992 and its follow-up summits in Berlin in 1995 and in New York in 1997, environmentalists have set targets for international co-operation and action. The paper identifies the particular segments of green consumers and explores the problems and opportunities that the green marketing businesses have in Bangladesh. It also examines the present trends of green marketing in Bangladesh and describes the reason why companies should adopt it. Further, it deals with the future of green marketing and concludes by studying consumer perception regarding green products in Bangladesh and also the business firm’s perception analysis.